AMERICAN ENGLISH (British Journal of Global Ecology and Sustainable Development, 2023)
American English, also known as U.S. English, is a variety of the English language spoken by citizens of the United States. It is the most widely spoken version of English in the country and has its own distinct accent, vocabulary, grammar rules, and cultural expressions. This article will explore the history of American English, its characteristics, and notable features.